Stigma pada tokoh utama dalam Novel 813 karya Maurice Leblanc - Adelia, Rahma; Lustyantie, Ninuk; Tri Widyastuti, Wahyu (Program Studi Pendidikan Bahasa Prancis FBS UNJ, 2022)
The purpose of this study is to describe the phases of stigmatizing the main character in the novel 813 by Maurice Leblanc. The approach used is a structural qualitative approach to literary works with content analysis methods. Data in the form of words, phrases or sentences, dialogue about the phases of stigma formation. While the data source is Novel 813 by Maurice Leblanc. The theory used in this study refers to the stigma theory according to Jean-Yves Giordana in the form of three phases of stigma formation, namely (1) the labeling phase (Étiquetage) (2) prejudice (Préjudice), and (3) discrimination (Discrimination). Data analysis uses document studies and refers to data analysis techniques for data sources, namely by analyzing each intrinsic element in the novel starting from plot, character and setting, then referring to data analysis techniques used by Miles and Huberman, namely, data reduction, data presentation and drawing conclusions. The results of this study indicate that there are twenty-two (22) quotations that show a stigma- forming phases felt by the main character in Maurice Leblanc's novel 813. Among them, the first phase of prejudice amounted to eleven (11) citations, the labelling phase consisted of seven (7) citations and the discrimination phase consisted of four (4) citations. Based on the research that has been completed, it can be concluded that the prejudice phase is the phase most experienced by the main character in Maurice Leblanc's novel 813, followed by the second phase, the labelling phase and the last phase, the discrimination phase.